Changes in the vascular cell adhesion molecule-1, intercellular adhesion molecule-1 and c-reactive protein following administration of aqueous extract of piper sarmentosum on experimental rabbits fed with cholesterol diet - Amran, A.A.; Zakaria, Z.; Othman, Faizah; Das, S.; Al-Mekhlafi, Hesham Mahyoub; Nordin, N. (2011)
Background: Inflammation process plays an important role in the development of atherosclerosis. Hypercholesterolemia is one of the major risk factors for atherosclerosis. The present study aimed to evaluate the effect of aqueous extract of Piper sarmentosum (P.s) on inflammatory markers like vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and C-reactive protein (CRP). Methods: Forty two male New Zealand white rabbits were divided equally into seven groups; (i) C-control group fed normal rabbit chow (ii) CH-cholesterol diet (1 cholesterol) (iii) X1-1 cholesterol with water extract of P.s (62.5 mg/kg) (iv) X2-1 cholesterol with water extract of P.s (125 mg/kg (v) X3-1 cholesterol with water extract of P.s (250 mg/kg) (vi) X4-1 cholesterol with water extract of P.s (500 mg/kg) and (vii) SMV group fed with 1 cholesterol supplemented with simvistatin drug (1.2 mg/kg). All animals were treated for 10 weeks. Blood serum was taken for observing the inflammatory markers at the beginning and end of the experiment. Results: Rabbits fed with 1 cholesterol diet (CH) showed significant increase in the level of VCAM-1, ICAM-1 and CRP compared to the C group. The levels of VCAM-1, ICAM-1 and CRP in the 1 cholesterol group and supplemented with P.s (500 mg/kg) were significantly reduced compared to the cholesterol group. Similar results were also reported with simvistatin group. Conclusion: These results suggest that the supplementation of Piper sarmentosum extract could inhibit inflammatory markers which in turn could prevent atherosclerosis.